The Affirmations of Reason On Karl Barth's Speculative Theology - Baark, Sigurd (Springer International Publishing, 2018)
This book examines the speculative core of Karl Barth's theology, reconsidering the relationship between theory and practice in Barth's thinking. A consequence of this reconsideration is the recognition that Barth's own account of his theological development is largely correct. Sigurd Baark draws heavily on the philosophical tradition of German Idealism, arguing that an important part of what makes Barth a speculative theologian is the way his thinking is informed by the nexus of self-consciousness, reason and, freedom, which was most fully developed by Kant, Fichte, and Hegel. The book provides a new interpretation of Barth's theology, and shows how a speculative understanding of theology is useful in today's intellectual climate.